La inteligencia lógica matemática y su incidencia en el rendimiento académico de los estudiantes de bachillerato general unificado de la Unidad Educativa La Mana, primer quimestre, período 2016 – 2017. - Chávez Vargas, Darío (2016)
The present research work contains very important aspects that can be applied to improve academic performance in the area of mathematics if it is possible to strengthen mathematical logical intelligence in high school students. Because mathematics is the subject in which students, both primary and secondary, present the greatest difficulties of learning and this happens practically all over the world, the present research that was carried out with students of unified general baccalaureate of the Educational Unit La Maná of La Maná canton in the province of Cotopaxi, seeks to relate the level of development of mathematical logical intelligence to the academic performance of those students. This work is based on the information obtained from specialized literature and on the application of the Upper Logic Intelligence Test that allowed to measure the degree of mathematical logical intelligence of the students that after being compared with the qualifications obtained in the first chemistry of the period 2016 - 2017, It was possible to prove with an error less than 5% stated that the results are valid and that this problem is urgent to solve it To exist, according to Gardner, eight types of intelligence that man can possess and see the world in eight different ways and know that one of them is logical intelligence mathematics, in addition to all humans have them in different degrees of intensity and That if we combine them, can help us perform different tasks or solve various problems, we realize that we are unique and able to achieve what we propose. The main purpose of this study is to analyze and interpret the results obtained after the application of the research instruments, which allows reaching conclusions that are in accordance with the objectives set.